Pengaruh Fasilitas Kamar dan Persepsi Harga Terhadap Kepuasan Tamu Menginap di Hotel Grand Tjokro Jakarta - Humairah, Wardatul; pasaribu, Pasaribu (Departemen Pariwisata Universitas Negeri Padang, 2025)
This research is motivated by problems with room facilities and price perceptions at the Grand Tjokro Hotel Jakarta which can affect guest satisfaction. This research aims to analyze the effect of room facilities and price perceptions on guest satisfaction staying at the Grand Tjokro Hotel Jakarta. This research uses a quantitative method with an associative approach in the form of a causal relationship using a survey method to determine the effect of room facilities and price perceptions on guest satisfaction. This research data was achieved through the use of research instruments in the form of questionnaires given to 103 respondents. The analysis of this research hypothesis uses multiple linear regression tests with the help of SPSS version 25.00. The results showed that room facilities (X1) had a positive and significant effect on guest satisfaction (Y). Likewise, price perceptions (X2) have a positive and significant effect on guest satisfaction (Y). This shows that the variable room facilities (X1) and price perceptions (X2) together have a significant effect on the guest satisfaction variable (Y).